2021
DOI: 10.3390/nu13093010
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hyperglycemia and Osteocalcin in COVID-19 Critically Ill Patients on Artificial Nutrition

Abstract: We aimed to study the possible association of stress hyperglycemia in COVID-19 critically ill patients with prognosis, artificial nutrition, circulating osteocalcin, and other serum markers of inflammation and compare them with non-COVID-19 patients. Fifty-two critical patients at the intensive care unit (ICU), 26 with COVID-19 and 26 non-COVID-19, were included. Glycemic control, delivery of artificial nutrition, serum osteocalcin, total and ICU stays, and mortality were recorded. Patients with COVID-19 had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…Low serum osteocalcin levels had been observed in two previous studies ( 12,13 ) Arrieta and colleagues ( 12 ) detected lower levels of osteocalcin in their SARS‐CoV‐2‐infected patients than ours, but unlike our cases theirs were critically ill patients on mechanical ventilation and were receiving glucocorticoids. Thus, inhibition of bone formation by glucocorticoids ( 18 ) may have accounted for the more pronounced reduction of osteocalcin in that study.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Low serum osteocalcin levels had been observed in two previous studies ( 12,13 ) Arrieta and colleagues ( 12 ) detected lower levels of osteocalcin in their SARS‐CoV‐2‐infected patients than ours, but unlike our cases theirs were critically ill patients on mechanical ventilation and were receiving glucocorticoids. Thus, inhibition of bone formation by glucocorticoids ( 18 ) may have accounted for the more pronounced reduction of osteocalcin in that study.…”
Section: Discussionsupporting
confidence: 45%
“…Two studies conducted so far showed reduced bone formation markers in critically ill and less severely ill COVID-19 patients. (12,13) When the present study was planned, we had no data on the potential effects of a COVID-19 disease on bone turnover. Therefore, the aim of this investigation was to evaluate bone turnover markers in COVID-19 patients needing hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…All of them are proinflammatory factors that orchestrates inflammation, fibrosis and tissue remodelling such as Tweak [50,51], or are involved in carcinogenesis such as April [52]. By contrast, osteocalcin [53] and IL-28A [54] were proposed to have beneficial metabolic and antiinflammatory properties. These results agree with a potential lowgrade metabolic stress induced by BS in the first phase of the intervention as it was previous proposed [24,25,55e58] that is improved in the long-term by the increase in beneficial metabolic factors [59].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, a study reported that deficiency of Ocn hormone impaired glucose homeostasis in Ocn null mice [ 3 ]. Of note, recently a study showed that lower levels of Ocn can be employed as a good prognostic marker for monitoring stress-induced hyperglycemia in COVID-19 infected patients [ 4 ]. In addition, exosomes-ExoFlo™ generated from bone marrow mesenchymal stem cells (MSCs-osteoblast progenitors) increased the survival rate in COVID-19 disease patients, by increasing oxygenation, reducing the inflammatory environment, and considerably lowering the neutrophil count [ 5 ].…”
Section: Introductionmentioning
confidence: 99%